The relationship between reproduction of the jump’s rhythm and technical score of their execution by gymnasts at the stage of initial training - Заплатинська, Оксана (Slobozhanskyi Herald of Science and Sport, 2016)
Oksana Zaplatynska Purpose: to determine the interconnection between quality of performance of the jumps and reproduction of the rhythm of jumps by gymnasts at the stage of initial training. Material & Methods: to determine the relationship between reproduction of rhythm and evaluation by the quality of technique of the jumps we used expert assessment, check the accuracy of the reproduction of rhythm with the help of computer program "rhythmic", methods of mathematical statistics. Results: the study found the correlation between reproduction of rhythm and summing-up of quality the technique of jumps by the gymnasts at the stage of initial training. Conclusions: the ability to reproduce a predetermined rhythm influences the level of technical readiness of gymnasts at the stage of initial training.